Pharmacognostic Evaluation And Hptlc Fingerprint Profile Of Curculigo Orchioides Gaertn. Rhizomes - PATIL, A.G.,; KOLI, S. P,; PATIL, D. A.,; PHATAK, A. V,; NARESH CHANDRA, (International Journal of Pharma and Bio Sciences, 2012)
Curculigo orchioides Gaertn. (Family: Hypoxidaceae) commonly known as Kali musli, the rhizomes of which are extensively utilized as nutritive tonic for strength and for treatment of asthma, skin diseases, bronchitis, diarrhoea, dyspepsia, etc. It also possesses anticancer and antipyretic activity. It is one of the important Rasayana drugs of Ayurvedic Materia Medica for vigor and vitality. It is also used in many Ayurvedic and Unani compound formulations as an important ingredient. Hence, the present work has been undertaken to establish the requisite pharmacognostic standards for evaluating the Curculigo orchioides Gaertn rhizome. In addition, HPTLC is also performed to detect the presence of β- sitosterol as the marker compound. The anatomical markers observed were bundles of acicular calcium oxalate crystals, lysigenous cavities, starch grains and vessel with spiral thickening. Preliminary phytochemical analysis showed presence of glycosides, mucilage, tannins, steroids, flavonoids, saponins and essential oils. Phytochemical analysis using HPTLC showed presence of arbutin, bitter principles, cardiac glycosides, coumarins, essential oils, lignans, pungent – tasting principles, saponins, triterpenes and valepotraites.